2020
DOI: 10.23822/eurannaci.1764-1489.133
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the Use of Tryptase in the Diagnosis of Anaphylaxis and Clonal Mastcell Disorders

Abstract: Tryptase is a serin-protease produced and released by mast cells after IgE-mediated or non-IgE mediated stimuli. We here review the various aspects related to the molecular characteristics of the enzyme and its biological effects, the genetic basis of its production and the release kinetics. Recommendations for the clinical use of tryptase measurement developed by a task force of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 53 publications
1
27
0
3
Order By: Relevance
“…A specific IgE value >0.10 kUA/L was considered positive. The sBT level was determined by using UniCAP Tryptase (Thermo Fisher Scientific, Uppsala, Sweden), with a normal value <11.4 ng/mL [15]. These tests were performed at least 3 weeks after venom exposure and resolution of the reactions.…”
Section: Methodsmentioning
confidence: 99%
“…A specific IgE value >0.10 kUA/L was considered positive. The sBT level was determined by using UniCAP Tryptase (Thermo Fisher Scientific, Uppsala, Sweden), with a normal value <11.4 ng/mL [15]. These tests were performed at least 3 weeks after venom exposure and resolution of the reactions.…”
Section: Methodsmentioning
confidence: 99%
“…Several epidemiologic and experimental studies [ 9 , 28 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] have underlined the importance of immunohistochemical analyses and the concentrations of serum tryptase; however, based on the literature, this article is the first study that combines the two parameters for a specific diagnosis of anaphylactic death.…”
Section: Discussionmentioning
confidence: 99%
“…Different sampling techniques can impact post-mortem tryptase levels [ 49 , 51 ]. A recent study demonstrated that the level of tryptase is significantly lower in samples collected via transcutaneous aspiration compared with femoral/external iliac vein samples [ 38 ]. In fact, for post-mortem tryptase analysis, a sample from a clamped femoral/external iliac vein should be defined as the gold standard [ 38 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“… 23 Similarly, Platzgummer states that in food anaphylaxis, tryptase levels are usually lower than those observed in drug-induced anaphylaxis. 24 …”
Section: Discussionmentioning
confidence: 99%